For Whom Does Hate Crime Hurt More? A Comparison of Consequences of Victimization Across Motives and Crime Types. Issue 3 (February 2021) - Mellgren, Caroline; Andersson, Mika; Ivert, Anna-Karin
Hate crimes have been found to have more severe consequences than other parallel crimes that were not motivated by the offenders' hostility toward someone because of their real or perceived difference. Many countries today have hate crime laws that make it possible to increase the penalties for such crimes. The main critique against hate crime laws is that they punish thoughts. Instead, proponents of hate crime laws argue that sentence enhancement is justified because hate crimes cause greater harm. This study compares consequences of victimization across groups of victims to test for whom hate crimes hurt more. We analyzed data that were collected through questionnaires distributed to almost 3, 000 students at Malmö University, Sweden, during 2013. The survey focused on students' exposure to, and experiences of, hate crime. A series of separate logistic regression analyses were performed, which analyzed the likelihood for reporting consequences following a crime depending on crime type, perceived motive, repeat victimization, gender, and age. Analyzed as one victim group, victims of hate crime more often reported any of the consequences following a crime compared with victims of parallel non–hate-motivated crimes. And, overall victims of threat more often reported consequences compared with victims of sexual harassment and minor assault. However, all hate crime victim groups did not report more consequences than the non–hate crime victim group. The results provide grounds for questioning that hate crimes hurt the individual victim more. It seems that hate crimes do not hurt all more but hate crimes hurt some victims of some crimes more in some ways.